Static behaviour of rammed earth: experimental testing and finite element modelling - Miccoli, L. (2015)
The paper presents an experimental program aiming at assessing the mechanical performance of rammed earth walls, namely under compression and shear loading. Axial compression and diagonal compression tests were carried out for this purpose, which allowed determining important mechanical parameters, such as compressive strength, Young’s modulus, Poisson’s ratio, shear strength and shear modulus. Furthermore, it allowed assessing the level of non-linear behaviour of the respective stress–strain relationships as well as the failure modes. The experimental results were then used in the calibration of numerical models (finite element method) for simulating the non-linear behaviour of rammed earth under shear loading. Both macro- and micro modelling approaches were considered for this purpose. The total strain rotating crack model was used to simulate the behaviour of the rammed earth material, while the Mohr–Coulomb failure criterion was used to simulate the behaviour of interfaces between layers. In general, the numerical models achieved good agreement with the experimental results, but uncertainties related to the definition of the input parameters required to perform a sensitivity analysis. The compressive strength, the Poisson’s ratio, the tensile strength and the tensile fracture energy revealed to be the most important parameters in the analyses.